Sensors for voltammetric determination of food azo dyes - A critical review; Electrochimica Acta; Vol. 260 - Lipskikh O. I. Olga Ivanovna; Korotkova E. I. Elena Ivanovna; Khristunova E. Ekaterina; Barek J. Jiri; Kratokhvil B. Bokhumil (2018, 2018)
Title screen